Gestión Sustentable De Riesgos Y Crisis En El Turismo Mexicano Y Latinoamericano Como Problema Estratégico Para La Seguridad De Los Destinos. Implicaciones Para Ciudad Juárez, México - Manuel Ramón González Herrera; Mercedes de los Ángeles Rodríguez Rodríguez (European Scientific Journal, ESJ, 2016)
The integrated management of risk and crisis in tourism has recently been incorporated to scientific debate and therefore to the practical management; which is why concepts and procedures are required to gain efficiency and practical operational development. The aim of this study is to justify the sustainable management process of risk and crisis in Mexican and Latin American tourism as a strategy for the security of destinations, and identify the experiences that promote a better preparedness and planning of risk and crisis caused by insecurity in Ciudad Juarez. The results of this study demonstrate that the integrated management of risk and crisis on tourism is justified as a strategic problem for security in tourist destinations, as well as the necessity to have policy and institutional framework to manage tourism safety. Then as a learning experience, an analysis of crisis and management strategies related to unsafe destinations in Latin America and Mexico are presented. Finally, the strategic projection for the preparation and planning of tourism, facing risks and crisis caused by insecurity in Ciudad Juarez is proposed. This includes the characterization of the city as an insecure cross-border tourist destination, the formulation of the strategic problem, the development of the principles to form a Sustainable and Secure Tourism System, and the planning of action areas for short-term and longterm implementation.